The Cytotoxic Effects of Ferula Persica var. Persica and Ferula Hezarlalehzarica against HepG2, A549, HT29, MCF7 and MDBK Cell Lines: Cytotoxicity of Ferula species - Homa Hajimehdipoor; Mahmood Mosaddegh; Somayeh Esmaeili; Azadeh Ramezani; Morteza Jafari Anaraki (Iranian Journal of Pharmaceutical Sciences, 2012)
Cancers belong to a group of disorders which are very important for researchers. Because they have several types and cause mortality in human beings. Many investigations are performing in order to introduce cheaper drugs with lower side effects especially with natural sources. Ferula genus grows all over the world but some of them are endemic to Iran. Many investigations have proved different biological activity of these plants. It has been established that some Ferula species have cytotoxic activity. In the present study, cytotoxic effects of F. persica var. persica and F. hezarlalezarica which are endemic to Iran have been evaluated against tumor cell lines MCF7, HepG2, HT29, A549, and a normal cell line MDBK using MTT method. Total extracts of the plants aerial parts were prepared by 80% methanol and maceration method. Different fractions of the plants were obtained using hexane, chloroform, ethyl acetate, pure or 50% methanol. Total extracts and different fractions were used for MTT assay. The results showed that among the examined samples, only hexane and chloroform fractions of the plants had cytotoxic effects up to concentration of 100 μg/ml. So that, extracts of F. persica var. persica were more cytotoxic than F. hezarlalezarica (IC50s, 22.3-71.8 μg/ml for F. persica var. persica and 76.7-105.3 μg/ml for F. hezarlalehzarica). It seems that both plants are suitable for further investigations in cancer researches.